Evaluation of rapid diagnostic test kits for feline leukemia virus infection using samples from naturally infected cats. Issue 2 (September 2016) - Liu, Jiayou; O'Connor, Thomas; Beall, Melissa; Chandrashekar, Ramaswamy; Lappin, Michael
Objectives: Feline leukemia virus (FeLV) is a potentially life-threatening oncogenic retrovirus. The p27 viral core protein is produced by the virus in infected feline cells, is found in the cytoplasm in several blood cells and can be free in the serum and plasma. ELISA or particle-based immunoassay are commonly used to detect the presence of the p27 core protein in samples obtained from blood. The objective of this study was to compare the performance of several in-clinic tests: the SNAP Feline Triple Test (IDEXX Laboratories), the WITNESS FeLV-FIV Test (Zoetis) and the VetScan Feline FeLV/FIV Rapid Test (Abaxis). Methods: The sample population (100 positive, 105 negative samples) consisted of serum and plasma samples submitted to IDEXX's worldwide reference laboratory for feline retrovirus testing. Virus isolation and reverse transcriptase PCR results were not available and so samples were judged to be positive or negative based on the results of the ViraCHEK FeLV (Zoetis) microtiter plate assay. Results: The percentage of samples positive and negative for FeLV p27 antigen using the three in-clinic tests compared with the ViraCHEK method were as follows: IDEXX Feline Triple (positive 98.0%, negative 100%); Zoetis WITNESS (positive 79.0%, negative 97.1%); Abaxis VetScan (positive 73.0%, negative 97.1%). Conclusions and relevance: The SNAP Feline Triple Test demonstrated a high level of agreement for FeLV-positive and FeLV-negative samples when assessed in this model. Results of FeLV assays can vary among tests.